(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cervical radiculopathy Syndrome (CRS) is a common neuro-musculo-skeletal disorder causing pain and disability. Manual therapy interventions including cervical traction with other treatment modalities have been advocated to decrease pain and disability caused by cervical radiculopathy (CR). Al-Qudah & AL-Jazzazi (2021) conducted a new method of Spinal Decompression Therapy (SDT) in patients with Chronic Lumbar Disc Herniation (CLDH) which includes Combination of Lumbar Traction With Cervical Traction (CLTCT) as one intervention. Despite of that this new method clinically reduces pain and disability more effectively than the conventional types of Traction, CLTCT method was not previously used in CR patients nor with Cervical Disc Herniation (CDH). The clinical effectiveness of this new method with other treatment modalities in patients with CRS was not approved yet. OBJECTIVE: The purpose of the presented work is to identify the effectiveness of rehabilitative program on patients with Cervical Radiculopathy, by (15) sessions for (4) Weeks. The suggested Rehabilitative program consisted of: 1.Supine Soft Full Back, Shoulders and Neck Cupping Massage (CM) for (10) minutes, 2.CLTCT: Combined Lumbar Traction with Cervical Traction as one intervention for (20) minutes, 3.Gradual Therapeutic Exercise Package of Neck Stretching and Strengthening Exercise for approximately (15) minutes. METHODS: In this study, Five outdoor male patients had accepted to participate and were randomly chosen from Al-Karak Governmental Hospital, All subjects applied the proposed rehabilitative program. The results were analyzed using the SPSS system. RESULTS: indicates that there was statistically significant difference between the pre and post measurements in favor of the post measurements in terms of Pain, Disability. CONCLUSIONS: The present study demonstrated that the use of proposed rehabilitative program has a positive effect on patients with Cervical Radiculopathy.